Psyche's daughter of today - Gadpaille, Michelle (ELOPE (Ljubljana), 2007)
The Canadian novelist Sara Jeannette Duncan (1861-1922) constructed a New Woman heroine in the fin-de-siecle novel, A Daughter of Today (1894). Written in the popular mode of the transatlantic novel, the work engages in debate on the appropriate construction of femininity in art and public life. The heroine, Elfrida Bell, descends from artist, to muse, to model, to painted image - a descent framed by a rival male artist and a hostile London art scene. Represented as Psyche, the heroine undergoes a quest and failure similar to the mythical one. Adaptation of the Psyche myth clarifies the position of Duncan in the spectrum of gender ideologies of the fin-de-siecle.
Keywords: Duncan, Sara Jeannette; Duncan, Sara Jeannette: A daughter of today; kanadska književnost; kanadska proza